Discrepancy Between Standing Posture and Sagittal Balance During Walking in Adult Spinal Deformity Patients. Issue 1 (1st January 2017) - Arima, Hideyuki; Yamato, Yu; Hasegawa, Tomohiko; Togawa, Daisuke; Kobayashi, Sho; Yasuda, Tatsuya; Banno, Tomohiro; Oe, Shin; Matsuyama, Yukihiro
Abstract : Study Design: Retrospective case series. Objective: The present study aimed to determine the characteristics of patients with adult spinal deformity (ASD) with a discrepancy between standing and walking postures. Summary of Background Data: Standing radiographic parameters are typically used to evaluate patients with ASD. Patients with ASD with relatively good sagittal alignment on standing radiography have, however, been reported to walk with a forward trunk tilt. Methods: Patients with ASD (n = 93; 13 men, 80 women; mean age, 65.0 yr) who underwent corrective surgery and preoperative gait analysis at our hospital between 2011 and 2013 were included. Spine radiographs and gait analysis data were acquired preoperatively. Standing-trunk tilt angle (STA) on lateral standing x-ray, gait-trunk tilt angle (GTA) from lateral gait images, and radiographic parameters of the spine and pelvis (lumbar lordosis [LL], pelvic tilt, and sagittal vertical axis) were measured. We calculated the increasing trunk tilt angle (ITA), by subtracting the STA from the GTA, for use as an index of discrepancy between standing posture and sagittal balance during walking. We examined the relation between radiographic parameters and ITA. Results: The mean preoperative STA and GTA were 3.5° and 11.1°, respectively. The mean preoperative ITA, which represents the degree of discrepancy between standing posture and sagittal balance during walking, was 7.6°. The mean preoperative sagittal vertical axis, LL, pelvic incidence (PI), pelvic tilt, and PI minus LL were 102.6 mm, 20.3°, 52.9°, 32.1°, and 32.6°, respectively. The PI minus LL mismatch was positively correlated with the ITA ( R  = 0.237, P  = 0.023). In particular, patients with ASD with a PI minus LL mismatch of more than 40° had a significantly greater ITA. Conclusion: Gait analysis revealed that a preoperative standing-walking discrepancy is associated with severe PI − LL mismatch. Level of Evidence: 4